Perceived Effects of the COVID-19 Pandemic on Loneliness: The Most Vulnerable Population Groups - Margarita Gedvilaitė-Kordušienė; Sarmitė Mikulionienė (Emerging Science Journal, 2023)
COVID-19 pandemic lockdown measures reasonably limited the social contacts of people in many countries. It is crucial to understand the effect of such policies on people’s social ties and the possible need for evidence-based public policy amendments. Therefore, this study examines 1) the prevalence of loneliness in the population aged 15+ in Lithuania in late 2021 and 2) the self-rated effect of the COVID crisis on loneliness in population groups with different levels of loneliness. It also focuses on the socio-demographic characteristics of these population groups. Data from a representative cross-sectional quantitative survey (N = 1067), carried out in November–December 2021, was used. Based on the 6-item De Jong Gierveld Loneliness Scale, descriptive statistics analysis revealed the high prevalence (51% of a medium level of loneliness) in the Lithuanian population. One in three people (36%) declared low-level loneliness, and each seventh or eighth (13%) reported high-level loneliness. The feelings of respondents who reported a high level of loneliness were also less stable; they more often stated that their feelings of loneliness increased during the pandemic. These research findings make contributions to studies of loneliness within the context of sudden crises. They emphasise the importance of policymakers focusing on additional measures when preparing for future emergencies and providing special attention to residents who experience the highest levels of loneliness. Doi: 10.28991/ESJ-2023-SPER-020 Full Text: PDF